Variation in Fitness of the Longhorned Beetle, Dectes texanus, as a Function of Host Plant - Michaud, J.P. (University of Wisconsin Library, 2010)
Dectes texanus LeConte (Coleoptera: Cerambycidae) has become a serious pest of two different crops in the American Midwest, sunflower, Helianthus annuus L. and soybean, Glycines max (L.). Laboratory and field studies were used to compare the effects of these two host plants on D. texanus life history and behavior. Insects from soybean were 40–60% smaller than those from sunflower and larval weight at collection was strongly correlated with survival to adulthood, whereas it was not in sunflower, suggesting that body size was more limiting to immature survival in soybean. Pupal weights increased more rapidly with increasing stem diameter in soybean than in sunflower and the correlation was stronger, indicating that body size was more limited by plant size in soybean. Adults collected as larvae from soybean had shorter longevities when starved, fed soybean, or fed an alternating diet of soybean and cultivated sunflower, than did those collected from sunflower, suggesting a negative larval legacy of soybean on adult fitness. Adult beetles that developed in soybean lived longer when fed soybean than when starved, but an adult diet of sunflower doubled longevity compared to soybean for beetles that developed in sunflower, and tripled it for those that developed in soybean. An adult diet of wild H. annuus yielded survivorship equivalent to cultivated H. annuus in one trial, and slightly lower in another. Larval host plant did not influence the numbers of ovipunctures or eggs laid by females in field trials, but adult diet did. Sunflower-fed females punctured more, and laid more eggs, on sunflowers than on soybeans in field cages and the reverse trend was evident, but not significant, in soybean-fed females. It can be concluded that H. annuus is a superior food source to G. max for both larval and adult D. texanus, and that wild sunflowers may represent a valuable food for adults during the pre-reproductive period, prior to invasion of soybean fields, even though they rarely host larvae. We also showed that stable isotope ratios of N can be used to distinguish the larval host plant of beetles regardless of their adult diet.